Can implant surfaces affect implant stability during osseointegration? A randomized clinical trial - CARMO FILHO,Luiz Carlos do (2018)
Abstract This randomized clinical trial evaluated the insertion torque (IT), primary, and secondary stability of dental implants with different surface treatments during the osseointegration period. Nineteen patients with bilateral partial edentulism in the posterior mandibular region were randomly allocated to two implant brand groups and received implants with different surface treatments in the opposite site of the arch: Osseotite and Nanotite or SLA and SLActive. During implant placement, the maximum IT was recorded using a surgical motor equipped with a graphical user interface. The implant stability quotient (ISQ) was assessed immediately after the IT, and was measured weekly via resonance frequency analysis during 3 months. The data were analyzed by a one-way ANOVA, the Bonferroni test, paired t tests and Pearson’s correlation coefficient. The IT values were similar (p > 0.05) for all implant types ranging from 43.82 ± 6.50 to 46.84 ± 5.06. All implant types behaved similarly until the 28th day (p > 0.05). Between 35 and 56 days, Osseotite and SLActive showed lower ISQ values (p < 0.001) compared to Nanotite and SLA implants. After 56 days, only Osseotite maintained significantly lower ISQ values than the other implants (p < 0.05). After 91 days the ISQ values were significantly higher than the baseline for all four implant types (p < 0.001). The ISQ and IT values were significantly correlated at the baseline and at the final evaluation for Osseotite, Nanotite, and SLActive implants (p < 0.001). After 91 days, ISQ and IT values were only significantly correlated for the Osseotite implants (p < 0.05). All implants types exhibited acceptable primary and secondary stability.